Niat Ibu Hamil Untuk Melakukan Inisiasi Menyusu Dini (IMD) di Puskesmas X Kota Surabaya - Siti Mafruchah (Jurnal Keperawatan Muhammadiyah, 2019)
Indonesia is a developing country that is making national development efforts in the health sector, one of which includes reducing the Infant Mortality Rate (IMR), by increasing the success of Exclusive Breastfeeding. Efforts made to achieve this coverage are with the Early Breastfeeding Initiation (IMD) program. The purpose of this study was to determine the intention of pregnant women to carry out Early Breastfeeding Initiation (IMD) at X Health Center Surabaya. This study used a type of phenomenological research with a qualitative approach using in-depth interview techniques. The main informants of this study were pregnant women of the third trimester who participated in the class of pregnant women at Puskesmas X Surabaya. Taking informants using purposive sampling techniques. The variables in this study were the characteristics of informants, self-confidence, and intentions. Characteristics of informants aged between 23 - 32 years. Based on the self-efficacy of the intention of pregnant women to carry out Early Breastfeeding Initiation (IMD), pregnant women are confident and capable because it is very important and good for the mother and child development. Another thing that supports the intention of pregnant women to carry out Early Breastfeeding Initiation (IMD) is family support, health workers, and the participation of pregnant women in the class of pregnant women. The conclusion of this study is that eight pregnant women all intend to carry out Early Breastfeeding Initiation (IMD), because it is very beneficial for mothers and children. Based on the results of the study, it is recommended to optimize the class of pregnant women to equalize information about Early Breastfeeding Initiation (IMD), start the class of pregnant women on time, maximize the transfer of knowledge about Early Breastfeeding Initiation (IMD) to pregnant women, evaluate the success of the coverage of Early Breastfeeding Initiation (IMD) regularly and periodically.